Political economy of sport broadcasting: Assessing Indonesian PSB policy in sport broadcasting. (March 2017) - Masduki,
The increasing presence of sport broadcasting on public service broadcasters in Indonesia is driven by a mixture of interests. It may serve as a tool for education and entertainment as well as for increasing awareness of 'symbolic nationalism'. Sport can also be used as a soft political campaign in the electoral system or even for pragmatic business purposes. This article assesses the sport broadcasting histories and policies of two Indonesian public service broadcasters: Radio of the Republic of Indonesia, and Television of the Republic of Indonesia. It assesses two political periods: the authoritarian period (1966–1998) and the transition towards a more liberal system (1998-present). Furthermore, this article critically examines both the political and economic interests behind the mediated sport policy. In addition, it intends to fill the gap in studies on sport policy, specifically public service broadcaster sport programming in transitional states. This study found that a change in the political structure resulted in unstable policies of sport broadcasting in Indonesian public broadcasters.